Efektivitas Komunikasi Kesehatan terhadap Tingkat Pengetahuan Ibu dalam Pencegahan Stunting - Sari, Rita Kartika; Ngatno, Ngatno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study was to evaluate the effectiveness of health communication in improving maternal knowledge about stunting prevention in the working area of ​​Kedung 1 Health Center, Jepara. The research method used a cross-sectional design involving 50 mothers with toddlers as respondents. Data on the level of knowledge before and after the intervention were collected through a questionnaire. Data analysis was carried out using the Wilcoxon Signed-Rank test. The results showed a significant increase in maternal knowledge scores after the health communication intervention. The average knowledge score increased from 9 (SD = 1.26) to 9.8 (SD = 0.4) with a p-value <0.001. This indicates that health communication is effective in improving maternal understanding of stunting prevention. The conclusion of the study is that health communication based on an emotional approach and the use of technology-based educational media has proven effective in improving maternal knowledge. The widespread application of this strategy can contribute to efforts to reduce the prevalence of stunting, especially in Indonesia. Keywords: Health Communication, Pregnant Mother, Stunting Prevention.